Contact allergy to acrylates and methacrylates in consumers and nail artists - data of the Information Network of Departments of Dermatology, 2004-2013 - Uter, Wolfgang; Geier, Johannes (Contact Dermatitis, 2015)
Allergic contact dermatitis caused by (meth)acrylates used in artificial nails is a relevant problem in both nail artists and consumers.To analyse the frequency of this problem in the contact allergy surveillance network Information Network of Departments of Dermatology in 2004-2013, and address possible time trends and patterns of co-sensitization.A retrospective analysis of patch test results with (meth)acrylates, along with clinical and demographic data, was performed. These were used to subdivide patients according to (i) a potentially exposed occupation and (ii) nail cosmetics as the suspected cause of contact dermatitis.Among the 114 440 patients patch tested, 72 244 were female and were considered further. Eighty-seven patients both worked as nail artists/cosmetologists and suspected nail cosmetics as the cause of dermatitis. Among these, 47.1% reacted to at least one (meth)acrylate, most often to 2-hydroxyethyl methacrylate (n = 27), 2-hydroxypropyl methacrylate, and hydroxyethyl acrylate (n = 26 each), with marked coupled reactivity. In other subgroups of interest, frequencies of sensitization to (meth)acrylates were less elevated but higher than in all remaining female patients (n = 69 419).The results indicate a not entirely common, but potentially serious, problem, especially concerning occupationally exposed, and sensitized, nail artists. Adequate protective measures should be taught as part of the vocational training.
EVALuna2:5511